1977
DOI: 10.1111/j.1528-1157.1977.tb04474.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbamazepine on the In Vitro Uptake and Release of Norepinephrine in Adrenergic Nerves of Rabbit Aorta and in Whole Brain Synaptosomes

Abstract: The effects of carbamazepine, in vitro, on adrenergic neuronal and whole brain synaptosomal uptake and release of tritiated norepinephrine (3H-NE) were assessed. At 10(-4) M, carbamazepine inhibited 3H-NE uptake by 22% in rabbit thoracic aorta and in brain synaptosomes. At the same concentration, carbamazepine inhibited stimulation-induced release of 3H-NE by 42.6% and inhibited isometric contraction in rabbit ear artery helical strips by 31.6%. At 10(-5) M, carbamazepine exhibited a 17.6% inhibition of 3H-NE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0
1

Year Published

1982
1982
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…Its main effect is related to DA release, since in the same concentration M ) it releases -60% of the accumulated [3H]DA. Modification of reuptake of another catecholamine, norepinephrine (NE), by CBZ has already been described (Purdy et al, 1977). It has been observed that CBZ inhibited more or less 20% of the reuptake of [3H]NE, in brain synaptosomes, at a concentration of M .…”
Section: Discussionmentioning
confidence: 97%
“…Its main effect is related to DA release, since in the same concentration M ) it releases -60% of the accumulated [3H]DA. Modification of reuptake of another catecholamine, norepinephrine (NE), by CBZ has already been described (Purdy et al, 1977). It has been observed that CBZ inhibited more or less 20% of the reuptake of [3H]NE, in brain synaptosomes, at a concentration of M .…”
Section: Discussionmentioning
confidence: 97%
“…However, unlike imipramine and desipramine, carbamazepine only weakly inhibits neuronal monoamine reuptake (16). In our studies of the reversal modulation of chloroquine resistance in W2 by car- bamazepine, carbamazepine had no intrinsic antimalarial activity at concentrations up to 10 p.g/ml and failed to modulate chloroquine resistance in W2 at concentrations up to 10 ,ug/ml (Table 1).…”
mentioning
confidence: 84%
“…However, unlike imipramine and desipramine, carbamazepine only weakly inhibits neuronal monoamine reuptake (16 …”
mentioning
confidence: 99%
“…The drug is chemically related to antidepressants (McNamara, 2001). In addition, the drug interacts with alpha adrenoceptors (Dilsaver et al, 1993;Mosqueda-Garcia, 1991) and decreases noradrenaline release (Purdy et al, 1977;Yoshimura et al, 1995). Some of the studies have shown that GABAergic systems are involved in the pharmacological property of carbamazepine (Waldmeier et al, 1995;Asahi & Yonehara, 2001).…”
mentioning
confidence: 98%